2010
DOI: 10.1088/0960-1317/20/6/064008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of temperature coefficients of resistance for uniformly doped P-type resistors in SOI

Abstract: Many today's microsystems like strain-gauge-based piezoresistive pressure sensors contain doped resistors. If one wants to predict correctly the temperature impact on the performance of such devices, the accurate data about the temperature coefficients of resistance (TCR) are essential. Although such data may be calculated using one of the existing mobility models, our experiments showed that we can observe the huge mismatch between the calculated and measured values. Thus, in order to investigate the TCR valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…9 (a). In doing so, α was 249 ± 16 ppm/K and β was 3.6 ± 0.1 ppm/K 2 (N = 4), which is in very good agreement with [5] (α between 200 and 400 ppm/K/β between 5 and 11 ppm/K 2 ). The temperature drift of the p-SOI Wheatstone bridge is shown in fig.…”
Section: Temperature Behaviorsupporting
confidence: 69%
See 1 more Smart Citation
“…9 (a). In doing so, α was 249 ± 16 ppm/K and β was 3.6 ± 0.1 ppm/K 2 (N = 4), which is in very good agreement with [5] (α between 200 and 400 ppm/K/β between 5 and 11 ppm/K 2 ). The temperature drift of the p-SOI Wheatstone bridge is shown in fig.…”
Section: Temperature Behaviorsupporting
confidence: 69%
“…resistors) was (0.0153 ± 12.3 ×10 -6 ) Ωcm (5×10 18 cm 3 ) and for the p ++ -silicon (0.0044 ± 24,5×10 -6 ) Ωcm (2.5×10 19 cm 3 ), respectively. The specific doping concentration for the resistors was chosen for achieving the lowest temperature coefficient for uniformly doped p-type resistors in SOI [5]. After the doping process, contact pads were coated with a high-temperature stable metallization system (Ti/Pd/Au or Ti/TiN/Au).…”
Section: Fabricationmentioning
confidence: 99%
“…Cho et al studied the effect of temperature on the TCR value on heavily doped n-type resistors from C to 130 C. They concluded that a first-order TCR is adequate to model the function at high doping concentrations [35]. A similar conclusion is reached by Olszacki et al for p-type silicon, where the quadratic terms in were found to approach zero at high doping levels [36].…”
Section: Temperature Effectsmentioning
confidence: 81%
“…The presented TCRs in Figure 18 are the combined effects of all orders TCRs in addition to the local effect of the geometric features. Values of TCRs were collected from literature [ 20 , 22 , 30 , 37 , 40 , 42 ] to perform further comparison. A similar procedure was used to calculate the TCRs from the published literature using the appropriate figures.…”
Section: Resultsmentioning
confidence: 99%